A cross‐national comparison of mathematical problems on numbers and operations‐related topics in five countries. (1st February 2021) - Sianturi, Iwan Andi Jonri; Ismail, Zaleha; Yang, Der‐Ching
Abstract: The purpose of this study is to compare the differences of four essential aspects (i.e., representational forms, contextual features, cognitive demand levels, and response types) embedded in mathematical problems within the topics of numbers and operations in mathematics textbooks used in Finland, Indonesia, Malaysia, Singapore, and Taiwan. This study employed a content analysis method to analyze the four aspects in the most representative textbook from each country. Results showed varied development of the four aspects and indicated different priorities being emphasized in each country's textbook. For instance, Singaporean textbooks have the highest percentage of mathematical problems that require higher levels of cognitive demands. Textbooks in Indonesia, Malaysia, Finnish, and Singapore contain more opportunities to engage with purely mathematical forms, with a percentage higher than 40%. Other findings concerning the four aspects can help to understand students' potential engagement with mathematics teaching and learning at elementary schools in the five countries.